Architectural Structures in Diyarbakir And Its Surroundings During the Chalcolithic Period - Tiryaki, Sırrı; Miğal, Serdar (Okay PEKŞEN, 2026)
The primary objective of this study is to examine the general characteristics of the architectural structures that developed in Diyarbakır and its surroundings during the Chalcolithic Age from a multifaceted perspective. The study specifically seeks answers to the following questions: Did the commercial and cultural relations maintained with Mesopotamia have an impact on the architectural traditions established in the region? Furthermore, what elements of the Chalcolithic Age cultures that emerged and developed in Mesopotamia are reflected in the formation of architectural traditions in the field? The answers to these questions will undoubtedly yield important findings regarding the region's residential architecture. Indeed, with the Chalcolithic Age, mudbrick architecture gradually became widespread as a result of new settlement practices coming from Mesopotamia in the south. In addition to the dwellings built as a result of ongoing economic and cultural contacts, temple architecture, which was gradually becoming institutionalised, also developed. Findings from archaeological excavations conducted in modern times reveal that the social life observed in the Ancient Near East during the Chalcolithic Age and the associated cultural transformations can also be traced in Diyarbakır and its surroundings. In particular, the storage rooms, ovens, hearths and workshops uncovered in architectural structures were visible results of changes in social and economic conditions. Furthermore, the architectural fabric of the area during this period was shaped by the existence of numerous building complexes developed around the main structure. This architectural transformation also constituted the fundamental parameters of the social and cultural changes that emerged during the Chalcolithic Age. Consequently, the phenomenon of urbanisation, which was widespread in the Anatolian plains during this period, emerged as a result of the transformation experienced in architectural traditions.

Bu çalışmanın temel amacı Kalkolitik Çağ’da Diyarbakır ve çevresinde gelişen mimari yapıların, genel karakteristik özelliklerini çok yönlü bir bakış açısıyla ele almaktır. Çalışmada özellikle şu sorulara yanıtlar aranmaktadır: Sahada kurgulanan mimari geleneklerde Mezopotamya ile sürdürülen ticari ve kültürel ilişkilerin bir etkisi olmuş mudur? Ayrıca Mezopotamya da ortaya çıkan ve gelişim gösteren Kalkolitik Çağ kültürlerinin, saha üzerindeki mimari geleneklerin biçimlenmesine yansıyan unsurları nelerdir? Elbette bu sorulara verilecek cevaplar sonrasında bölgenin konut mimarisine ilişkin önemli bulgular elde edilecektir. Zira Kalkolitik Çağ’la birlikte güneydeki Mezopotamya’dan gelen yeni yerleşme pratiklerinin bir sonucu olarak kerpiç mimari giderek yaygınlaşmıştır. Sürdürülen ekonomik ve kültürel temaslar sonucunda inşa edilen konutların dışında giderek kurumsallaşmaya başlayan tapınak mimarisi de gelişmiştir. Modern dönemlerde gerçekleştirilen arkeolojik kazılar sonucunda elde edilen bulgular, Kalkolitik Çağ’da Eski Yakın Doğu’da gözlemlenen toplumsal yaşam ve buna bağlı kültürel dönüşümlerin Diyarbakır ve çevresinde de izlenebildiğini ortaya koymaktadır. Özellikle mimari yapılarda ortaya çıkarılan erzak depoları, fırın, ocak ve işlikler, toplumsal ve ekonomik koşullardaki değişimin görünür sonuçları olmuştur. Ek olarak bu dönemde alandaki mimari yapı dokusu ana mekân çevresinde gelişen birçok yapı kompleksinin varlığıyla şekillenmiştir. Söz konusu bu mimari dönüşüm aynı zamanda Kalkolitik Çağ’da ortaya çıkan toplumsal ve kültürel değişimlerin temel parametrelerini oluşturmuştur. Dolayısıyla bu dönemde Anadolu düzlüklerinde yaygın olarak görülen kentleşme olgusu, mimari geleneklerde yaşanan dönüşümün bir sonucu olarak ortaya çıkmıştır.
Kalkolitik Çağ’da Diyarbakır ve Çevresindeki Mimari Yapı
Keywords: Old Anatolian History; Eski Anadolu Tarihi